Expanding the Donor Pool: Experience of Living Kidney Transplantation from Very Old Aged Donor in Our Center. (July 2018) - Hirano, Hajime; Maenosono, Ryoichi; Matsunaga, Tomohisa; Uehara, Hirofumi; Nomi, Hayahito; Kano, Yosuke; Fujiwara, Yuya; Taniguchi, Shyunri; Tsutsumi, Takeshi; Ichihashi, Atsushi; Kobayashi, Daisuke; Ohkita, Kyohei; et al.
Abstract : Much controversy exists over the performance of elderly living donor kidney transplantation. We report on safety of elderly living kidney donors with a focus on two cases of the elderly living donors in kidney transplantation conducted in our hospital. Case 1. An 82-year-old male, a living kidney donor for his 56-year-old son. He suffered from hypertension, had successfully managed his blood pressure with only one antihypertensive drug. The serum creatinine was 0.7 mg/dl and inulin clearance was 122.5 ml/min, which met the usual criteria for living kidney donor. This was his secondary kidney transplantation, and no other donors existed. Case 2. An 80-year-old female is a living kidney donor for her 45-year-old son. The serum creatinine was 0.61 mg/dl and inulin clearance was 71.7 ml/min, and the marginal kidney donor criteria were met. In both cases, we determined that there were no problems with the donor's kidney function. We completely explained risks for the transplantation, but because they had a strong will to offer a kidney to his son, we decided to transplant. Around 2 years have passed since the transplantation, but both the donors and recipients are currently doing well. It seems more likely that the number of elderly living donor kidney transplantation will rise in future. On the one hand, there is no absolute contraindication, and on the other hand, the criteria for living kidney donor must be strictly examined. Furthermore, careful observation of both a donor and a recipient after transplantation is required.